Cardio-oncology - strategies for management of cancer-therapy related cardiovascular disease. (1st April 2019) - Totzeck, Matthias; Schuler, Martin; Stuschke, Martin; Heusch, Gerd; Rassaf, Tienush
Abstract: Current therapy of advanced cancers is based on several modalities including radiotherapy, cytotoxic chemotherapy, molecularly targeted inhibitors and antibodies targeting immune checkpoints. All of those these modalities can negatively impact the cardiovascular system, and there is considerable experience in relation to radiotherapy and chemotherapy. In contrast, the knowledge base on cardiovascular toxicities of novel agents targeting signal transduction pathways and immune regulation is quite limited. In particular, potential late effects are of concern as cardiovascular pathology can negatively impact quality of life and prognosis in cancer survivors, particularly when additional cardiovascular risk factors are present. Treatment-associated adverse events include hypertension, venous thromboembolism, coronary artery disease, valvular heart disease, heart failure and arrhythmias. Early diagnosis of subclinical cardiotoxic effects of cancer therapies remains challenging. Integrated care, as provided by multidisciplinary cardio-oncology teams is the best option for prevention, diagnosis and treatment of cardiovascular diseases associated with cancer therapy. This review considers the cardiotoxic effects of specific cancer therapies and discusses novel diagnostic and therapeutic approaches as a reference for optimizing the care of cancer patients receiving novel cancer therapies. Highlights: The risk for cardiotoxicity is incompletely defined particularly for novel cancer therapies. Adverse events include heart failure, coronary artery disease, hypertension, valvular heart disease and arrhythmia. Cardio-oncology provides a multi-disciplinary care approach for cancer patients with cardiovascular diseases. Propose therapeutic algorithms for distinct cancer therapies based on recent findings and guideline recommendations